Petro Populism - Egil Matsen; Gisle James Natvik; Ragnar Torvik (Norges Bank, 2012)
We aim to explain petro populism - the excessive use of oil revenues to buy political support. To reap the full gains of natural resource income politicians need to remain in office over time. Hence, even a purely rent-seeking incumbent who only cares about his own welfare, will want to provide voters with goods and services if it promotes his probability of remaining in office. While this incentive benefits citizens under the rule of rent-seekers, it also has the adverse effect of motivating benevolent policymakers to short-term overprovision of goods and services. In equilibrium politicians of all types indulge in excessive resource extraction, while voters reward policies they realize cannot be sustained over time. Our model explains how resource wealth may generate political competition that reduces the tenability of equilibrium policies.
hdl:11250/2496833
Keywords: D72; O13; Q33; 330; resource curse; political economy